Adolf Bibič’s innovative contribution to the marxist conceptualisation of politics - Hočevar, Marko (Teorija in praksa, 2024)
The article analyses the innovative Marxist conceptualisation of politics proposed by the Slovenian political scientist Adolf Bibič. The latter built on the contributions of Heglo-Marxists and Gramsci to political theory. At the core of his theory, he placed the question of the political power–class exploitation relationship. He distinguished political politics from self-managing politics, and problematised the dominant Western understandings of politics as well as the theories of elitism and pluralism. Moving away from such theories and dogmatic Marxist notions about the withering away of politics, he formulated his project of humanising politics beyond class exploitation and capitalist relations of production. This project assumed a necessary transformation of political practice in terms of the dialectical process of the socialisation of politics and the politicisation of society.
Keywords: Bibič, Adolf; class relations; economic exploitation; ekonomsko izkoriščanje; politics; Politične vede; politika; razredni odnosi